2015
DOI: 10.1007/jhep11(2015)157
|View full text |Cite
|
Sign up to set email alerts
|

Einstein-Born-Infeld-massive gravity: adS-black hole solutions and their thermodynamical properties

Abstract: In this paper, we study massive gravity in the presence of Born-Infeld nonlinear electrodynamics. First, we obtain metric function related to this gravity and investigate the geometry of the solutions and find that there is an essential singularity at the origin (r = 0). It will be shown that due to contribution of the massive part, the number, type and place of horizons may be changed. Next, we calculate the conserved and thermodynamic quantities and check the validation of the first law of thermodynamics. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 90 publications
(122 reference statements)
0
76
0
Order By: Relevance
“…[63][64][65][66]. Furthermore, it was shown that the mentioned massive gravity has sensible effects in metal/superconductor phase transition.…”
Section: Jhep05(2016)029mentioning
confidence: 98%
See 2 more Smart Citations
“…[63][64][65][66]. Furthermore, it was shown that the mentioned massive gravity has sensible effects in metal/superconductor phase transition.…”
Section: Jhep05(2016)029mentioning
confidence: 98%
“…[62]. Moreover, the generalizations of such theory to include nonlinear electrodynamics, higher derivative gravity and gravity's rainbow have been done [63][64][65][66]. In addition, thermodynamic properties, phase transitions and thermal stability of such generalized models have…”
Section: Jhep05(2016)029mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the electromagnetic field tensor indimensions is given by tr = √ 2 3 /(1 + Γ)( / 2 ), and the metric function ( ) is obtained as follows [58]: ,…”
Section: Thermodynamics Of -Dimensional Born-infeld Ads Black Holesmentioning
confidence: 99%
“…More discussions in various gravity theories can be found in . Recently, some investigations for thermodynamics of AdS black holes have been also generalized to the extended phase space in the dRGT massive gravity [47][48][49][50], which show the Van der Waals-like SBH/LBH phase transition in the charged topological AdS black holes. In addition, the deep relation between the dynamical perturbation and the Van der Waals-like SBH/LBH phase transition in the fourdimensional dRGT massive gravity has been also recovered in [51].…”
Section: Introductionmentioning
confidence: 99%